The association between chronic disease and work productivity among public health staff in Kota Bharu district - Mohd Emeran, Nurul Ain (2015)
Work productivity of public health staff is as much as crucial as other production labor force to ensure the empowerment of healthy nation, healthy human capitals thus contribute to high economic growth of our country since they are involved in promotion of healthy lifestyle, control and prevention of communicable and noncommunicable diseases. The objective of this study was to determine the proportion of chronic diseases and its association with work productivity among public health staff in Kota Bharu District. This is a cross sectional study done among 363 public health staffs using pro forma checklist which consist of socio-demographic data, status of chronic diseases, annual and medical leaves data and measuring presenteeism level using Stanford Presenteeism Scale questionnaire. The study showed the prevalence of dyslipidemia was 19.3%, hypertension 16.0%, asthma 12.7%, diabetes mellitus 11.6% and arthritis 5.0%. About 70% of staffs reported to have low work productivity for the past one year. There were 89% of staffs reported with high presenteeism, 62.5% absenteeism, and 1.4% with high sickness absence. Multiple logistic regression analysis showed that dyslipidemia (AOR 11.86, 95% CI: 2.76, 50.50; p = 0.001), hypertension (AOR 3.43, 95% CI: 1.13, 10.35; p = 0.029) and diabetes mellitus (AOR 5.40, 95% CI: 1.54, 18.99; p = 0.009) were significantly associated with low work productivity. However, there was no significant association was found between asthma, arthritis and other chronic diseases with low work productivity. This study demonstrated that chronic diseases can contribute to low work productivity affecting the quality of public health program.